Pengaruh Faktor Individu dan Faktor Lingkungan terhadap Prestasi Kerja Karyawan pada PT. Lion Mentari Airlines Kota Semarang - Siti Fatimah; Suhaji Suhaji (STIE Widya Manggala, 2013)
This study aimed to analyze the influence of individual factor and environmental factor on the employeesperformance at PT. Lion Mentari Airlines Semarang. In this study the population is 45 employees, with a total sample of 45 employees. The sampling technique used is census. Data collection methods in this study were primary and secondary. Data was analyzed with the classical assumption test that includes tests of normality, multikolonierity, heteroscedasticity. Data analysis techniques used in this study was multiple linear regression analysis. The partial test of the hypothesis results partially showed that individual factor (7,330 t value >t table 2.0181) and environmental factor (2,442 t value >t table 2.0141) had a significant influence on employees performance. While ontest of the hypothesis results simultaneously showed that the individual factor and environmental factor had a significant influence on employees performance, proved bythe F value 39,432 >F Table 3.22 and the influence was 63,6%.